On Tragedy of Commons, State Sovereignty and BBNJ Treaty: Reconnoitring for Harmony - Arindam Basu; Sharda Mandal; Ananya Das (Lex Portus)
Garrett Hardin’s ‘Tragedy of the Commons’ may be almost half a century old. But the centrality of the theory is still relevant for the environmental challenges associated to the management of global commons. In this article, we examine the newly adopted treaty for the conservation of marine biological diversity in areas beyond national jurisdiction (BBNJ) in the light of Hardin’s basic postulation that a tragedy eventually materializes following an indiscriminate use of resources freely available to all and used to pursue self-interests. Today, the problem transcends beyond self-seeking state actions and analogous cost-benefit inquiry. A deeper examination is absent largely from the analytical framework of commons management, leaving an important question unanswered – how far does the concept of state sovereignty hold the potential to alter the boundary of the legal framework on global commons, thinning the theoretical underpinnings of the ‘tragedy’ itself? This in effect reduces the transparency of choices and reduces the incentives of states to negotiate a strong global agreement for commons. Because the BBNJ Treaty is expected to upgrade the legal framework of the United Nations Convention on Law of the Sea (UNCLOS), it is desirable to compare the structural features of both. It is our argument that the BBNJ Treaty has failed to alter the boundary of state sovereignty or sovereign rights sufficiently to advance a novel solution towards the problems of high sea commons. The challenges that frustrated UNCLOS to cast a strong protective net over high seas, resurfaced and gridlocked BBNJ Treaty, too. As, conservation and management of common resources leaves narrow space for all nations irrespective of their positions in international politics, there is a need to revisit the pitch of negotiation to avoid any further ‘tragedy’ that already has turned up high seas a battleground for interest-negotiation.